Bed nuclei of the stria terminalis: A key hub in the modulation of anxiety. (16th February 2023) - Wang, Xinxin; Ge, Shenglin; Zhang, Chengxin
Abstract: The bed nuclei of the stria terminalis (BST) is recognised as a pivotal integrative centre for monitoring emotional valence. It is implicated in the regulation of diverse affective states and motivated behaviours, and decades of research have firmly established its critical role in anxiety‐related behavioural processes. Researchers have recently intricately dissected the BST's dynamic activities, its connection patterns and its functions with respect to specific cell types using multiple techniques such as optogenetics, in vivo calcium imaging and transgenic tools to unmask the complex circuitry mechanisms that underlie anxiety. In this review, we principally focus on studies of anxiety‐involved neuromodulators within the BST and provide a comprehensive architecture of the anxiety network—highlighting the BST as a key hub in orchestrating anxiety‐like behaviour. We posit that these promising efforts will contribute to the identification of an accurate roadmap for future treatment of anxiety disorders. Abstract : The BST is a highly heterogeneous brain region in the limbic system that contains multiple genetically distinct neuronal subgroups. It serves as a key hub for the integration of various central and peripheral information, and orchestrates anxiety‐related behavioural responses to the environment via diverse cell types, as well as complicated local and long‐range neuronal circuits.